Green space exposure and Chinese residents’ physical activity participation: empirical evidence from a health geography perspective - Xia, Qi-fei; Qin, Guo-you; Liu, Qi; Hu, Yun-zhou (Frontiers in Public Health, 2024)
Background: With continuous efforts made to promote the strategic goals of carbon neutrality and carbon peak, it is crucial to meet the growing and diversified needs of the public for fitness by practicing the concept of green development and promote the combination of national fitness and ecological civilization.Methods: To achieve this purpose, an OLS regression model was applied to estimate the role of green space exposure in Chinese residents' participation in physical activity and its underlying mechanisms, using the microdata from the China General Social Survey (CGSS) data and the Provincial Vegetation Cover Index (NDVI) matched macro-statistical data.Results: The empirical results show that green space exposure significantly increases the probability of residents' physical activity participation, and creating a green environment is conducive to creating a favorable physical activity environment for residents. Also, the core conclusions still hold after the year-by-year regression test is passed and the endogeneity problem is addressed. As revealed by mechanistic studies, green space exposure has indirect effects on the physical activity participation of residents through the independent mediating roles of reducing carbon emissions and promoting social interaction. According to heterogeneity results, males, those in marriage, and urban dweller groups are more inclined to perform physical activity in green spaces.The results show that the exposure of green space can help increase the probability of residents' participation in physical exercise, and can that it achieved through two channels: reducing carbon emissions and enhancing social interaction. It is necessary to further strengthen the protection of the ecological lifestyle, give full play to the advantages of greenness and low-carbon, and create favorable conditions for the green development of a new model of national fitness.